Neonatal Acute Megakaryoblastic Leukemia Presenting with Leukemia Cutis and Multiple Intracranial Lesions Successfully Treated with Unrelated Cord Blood Transplantation. (1st July 2015) - Tsujimoto, Hiroshi; Kounami, Shinji; Mitani, Yasuyuki; Watanabe, Takashi; Takifuji, Katsunari
Abstract : Neonatal acute megakaryoblastic leukemia (AMKL) without Down syndrome (DS) is an extremely rare disorder. We report of a one-day-old male infant without DS who developed AMKL with leukemia cutis and right facial nerve palsy. Magnetic resonance imaging of the patient's brain revealed multiple intracranial tumors. A biopsy specimen of the skin lesion was suggestive of AMKL, but the bone marrow leukemic cells were less than 5% of the marrow nucleated cells. The skin and intracranial lesions had spontaneously regressed within one and a half months, but the patient's anemia and thrombocytopenia gradually worsened and the leukemic cells in the bone marrow gradually increased to more than 20% of the nucleated cells. In addition, multiple intracranial lesions reappeared at 72 days of life. We diagnosed the patient with AMKL, and chemotherapy followed by unrelated cord blood transplantation after a reduced-intensity conditioning regimen resulted in sustained complete remission. At present, the patient is well, and he has demonstrated normal development for five years.